2018
DOI: 10.1016/j.psychsport.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Teeing up for success: The effects of rational and irrational self-talk on the putting performance of amateur golfers

Abstract: The investigation of rational emotive behaviour therapy (REBT) in sport settings is growing, but controlled experimental field studies are sparse. In the limited extant literature, researchers have found that irrational (extreme, rigid, and illogical) self-talk leads to disrupted motor skill performance, compared to rational (non-extreme, flexible, and logical) self-talk. However, methodological limitations of past research and the absence of sport-relevant tasks limit the application of findings to athletic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
0
19
0
5
Order By: Relevance
“…The current sample also involves higher proportion of male golfers in comparison to females. The sex-imbalance with the sport of golf, with 15% of golf club members being female (England Golf, 2018) makes it difficult to make comparisons, therefore future research should look at recruiting equal numbers of males and females for a detailed comparisons (Turner et al, 2018b). In addition, the substantial time delay from completion of the questionnaires to the next competition for some golfers meant that there is great variability in the time to event data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current sample also involves higher proportion of male golfers in comparison to females. The sex-imbalance with the sport of golf, with 15% of golf club members being female (England Golf, 2018) makes it difficult to make comparisons, therefore future research should look at recruiting equal numbers of males and females for a detailed comparisons (Turner et al, 2018b). In addition, the substantial time delay from completion of the questionnaires to the next competition for some golfers meant that there is great variability in the time to event data.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study (Evans et al, 2018) found that soccer athletes who received a rational team talk (promoting rational beliefs) at half-time reported significantly lower threat compared to athletes who received an irrational team talk (promoting irrational beliefs). Research has also examined the effect of irrational and rational beliefs on performance within golf (Turner et al, 2018a, b). One study (Turner et al, 2018b) found that when golfers used rational self-talk they performed more accurately in a putting task than when they used irrational self-talk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from challenge and threat research have demonstrated that imagery scripts can differentiate between challenge and threat states (Williams et al, 2010) rather than just focusing on using imagery to manipulate challenge and threat states; this can be built on to strengthen challenge states. Also, based on the emerging evidence that irrational beliefs, as proposed within REBT, are related to greater threat (Dixon et al, 2017;Evans et al, 2018), and that rational self-talk has been shown to increase performance under pressure (Turner et al, 2018), REBT could be applied with athletes in order to promote rational beliefs, and subsequent challenge appraisals. Indeed, the use of REBT in sport is growing (Turner, 2016), with some research finding that systolic blood pressure is reduced in athletes following REBT (Wood et al, 2018a).…”
Section: Enhancing Resourcesmentioning
confidence: 99%
“…Los deportistas en ocasiones sufren una alta exigencia cuando compiten, debiendo de rendir al máximo nivel (Núñez y García-Mas, 2017). Esto provoca una presión, a veces perjudicial, para el rendimiento (León-Prados et al, 2011;Ramis et al, 2010;Tobar, 2014;Turner et al, 2018). Por eso es muy importante el entrenamiento, que implica un gran esfuerzo permanente durante largas jornadas, sometiendo al organismo a cargas físicas y psíquicas con el objetivo de incrementar la capacidad de trabajo hasta el punto de realizar grandes esfuerzos, para obtener el máximo rendimiento cuando se compite (Valdés, 1996).…”
unclassified